The impact of a vestibular-stimulating exercise regimen on postural stability in women over 60 - Ida Wiszomirska; Katarzyna Kaczmarczyk; Michalina Błażkiewicz; Andrzej Wit (Elsevier, 2015)
Background/Objective: The aim of this study was to assess whether a program of exercise specifically designed to target the vestibular organ improved the postural stability of female participants over 60 years old. Methods: Twenty-eight healthy female volunteers aged from 60 years to 76 years were assigned to a group (n = 15) engaging in vestibular-stimulating exercises, or to a control group (n = 13) engaging in traditional training exercises. Training sessions (∼45 minutes each) occurred twice a week over the course of 3 months. The following parameters were analyzed before and after training for both groups: stabilogram ellipse area and radii, total length of stabilogram, and visual-inspection indicator (eyes open). Results: Results in terms of stabilogram ellipse area and radius without visual control (eyes closed) revealed statistically significant differences in the experimental group between the values before and after the training regimen (74.8 ± 51.6 − 54.5 ± 42.5 for area of ellipse, 6.6 ± 2.8 − 5.8 ± 2.8 for axis minor, 13.2 ± 4.3 − 11.1 ± 3.3 for axis major, respectively). No significant changes were observed in the control group. Conclusion: Exercises stimulating the vestibular organ, such as those described herein, should be a part of efforts to improve balance in older people.